2009
DOI: 10.1016/j.febslet.2009.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Profiling CD antigens on leukaemias with an antibody microarray

Abstract: Edited by Miguel De la RosaKeywords: Leukaemia Lymphoma Cluster of differentiation antigen Microarray a b s t r a c t Cluster of differentiation (CD) antigens are defined when a surface molecule found on some members of a standard panel of human cells reacts with at least one novel antibody, and there is good accompanying molecular data. Monoclonal antibodies to surface CD antigens on leukocytes have been used for flow cytometry, and more recently to construct microarrays that capture live cells. These DotScan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Proof of principle of this technology in leukemia diagnosis has already been reported [2]. Another approach uses antibody microarrays based on a solid phase cell-capture technique [3], [4]. Belov L et al reported the analysis of the simultaneous expression of eighty-two antigens in 733 patients with a variety of leukemias and lymphomas, achieving a high degree of diagnostic consensus between established criteria and the results of an antibody microarray (93.9% for peripheral blood and 97.6% for bone marrow aspirates) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Proof of principle of this technology in leukemia diagnosis has already been reported [2]. Another approach uses antibody microarrays based on a solid phase cell-capture technique [3], [4]. Belov L et al reported the analysis of the simultaneous expression of eighty-two antigens in 733 patients with a variety of leukemias and lymphomas, achieving a high degree of diagnostic consensus between established criteria and the results of an antibody microarray (93.9% for peripheral blood and 97.6% for bone marrow aspirates) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of using array separation devices is that the volume of the array fluidic chamber is typically well known, allowing for absolute cell counting and eliminating the need for counting beads or an additional counting step – a large bottle neck in separations today. Affinity arrays have been extensively developed for characterization of blood cells and other cells based on antibody–antigen capture (Barber et al, 2009, Kaufman et al, 2010, Kohnke et al, 2009, Rahman et al, 2012, Zhou et al, 2010). …”
Section: Overview Of Cell Separation Methodsmentioning
confidence: 99%
“…Complex CD antigen phenotyping is achievable with DotScan TM [4,5], by printing cell surface antigen-specific antibodies onto the array, then incubating the slide in cell suspension, and finally visualizing bound cells. The binding pattern indicates which CD antigens are expressed on the cell membrane.…”
Section: Determination Of Cluster Of Differentiation (Cd) Antigensmentioning
confidence: 99%